Errors in translation: a comparative study of noun phrase in English and Malay abstracts - Md Zamin, Ainul Azmin; Abu Hasan, Raihan (Australian International Academic Centre PTY.LTD, 2018)
Abstract as a summary of a dissertation harbours important information where it serves to attract readers to consider reading the entire passage or to abandon it. This study seeks to investigate the backward translation of abstracts made by 10 randomly selected postgraduate students. This research serves as a guideline for students in composing their abstracts as it aims to compare the differences in noun phrase structure written in Malay as translated from English. It also analyses the types of errors when English noun phrases are translated to Malay. Preliminary findings from this pilot study found that translation errors committed were mainly inaccurate word order, inaccurate translation, added translation, dropped translation and also structure change. For this study, an exploratory mode of semantic analysis is applied by looking at noun phrases, the meaningful group of words that form a major part of any sentence, with the noun as the head of the group. Syntax is inevitably interwoven in the analysis as the structure and grammatical aspects of the translations are also analysed. They are examined by comparing English texts to its corresponding translation in the Malay language. Particularly relevant in this study is the need to emphasize on the semantics and syntax skills of the students before a good transaltion work can be produced. Language practitioners can also tap on translation activities to improve the learners’ language competency